Odpowiedzi

2009-10-21T18:16:45+02:00
Przypomnij sobie wzór a² - b² = ( a + b )( a - b )
( 1/2 z - 4 )( 1/2 z + 4 ) ----- powiedzmy że 1/2z to będzie a , a b to 4
( 1/2z )² - ( 4 ²) = z²/4 - 4 = z² - 16

( 3/4ab - 5c)(5c + 3/4ab) = ( 3/4ab - 5c)(3/4ab + 5c) = (3/4ab)² - (5c)² =
9a²b²/16 - 25c² = 9a²b² - 400c²

(2a + 3b)(2a - 3b) = (2a)² - (3b)² = 4a² - 3b²

(5x - y)(y + 5x) = ( 5x - y )( 5x + y) = (5x)² - (y)² = 25x² - y²

(1,5a + 0,2b)(1,5a - 2b) = (1,5a)² - (2b)² = 2,25a² - 4b²

(1 i 1/2x²y - 0,5z)(1i 1/2x²y + 0,5z) = (1 i 1/2x²y )² - (0,5z)² = (3/2x²y)²- 0,25z² = 9/4xdo potęgi czwartej razy y² - 1/4z² = 9x do czwartej razy y² - z² /4